PENGARUH KONSENTRASI DAN LAMA PERENDAMAN KNO3 TERHADAP PERKECAMBAHAN BENIH KOPI ARABIKA ( Coffea arabica L. ) - Brian C Sirait (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2020)
Coffee plants germinate slowly due to physical barriers and hard seed coat so that water and oxygen are difficult to penetrate the seed coat which results in stunted embryo growth. Therefore the dormancy breaking technique is needed using a chemical that is KNO3. The use of KNO3 must pay attention to soaking time so as not to damage the embryo. This research was conducted in November 2019 to February 2020 in the Basic Laboratory of Agronomy, Faculty of Agriculture, University of North Sumatra Medan, using a randomized block design with two treatment factors. The first factor is the concentration of KNO3 with 4 levels namely ; 0%, 0.25%, 0.5%, and 0.75%, the second factor is soaking time with 3 levels namely ; 20 hours, 24 hours and 28 hours. Observation parameters are the percentage of germination, germination rate, vigor index, root length, hypocotyl length, wet weight, and dry weight. The results showed that the concentration of KNO3 significantly affected the root length parameter but it has no significant effect on other parameters. The KNO3 soaking time significantly affected the parameters of the percentage of germination, germination rate and vigor index but it has no significant effect on other parameters. The interaction between the two treatments did not significantly affect all parameters.